When Conflict be a Trigger of Depression: between Job and Life Satisfaction - Sulimah, Sulimah; Wulansari, Nury Ariani (JDM (Jurnal Dinamika Manajemen), 2018)
The objective of this study is to investigate the effect of work-family conflict and family-work conflict on depression behavior mediated by job satisfaction and life satisfaction. The respondents in this research were 133 female nurses in two public hospitals in Indonesia. Methods of data collection were by using observation, interviews, and questionnaires. The sampling technique used the technique of proportional random sampling. Methods of data analysis were by using factor analysis, regression analysis and path analysis. Data analysis were by using SPSS software version 21. The results show that all hypothesis in the research were supported. Work-family conflict has an effect on depression behavior either directly or mediated by job satisfaction and life satisfaction. Similarly, the work-family conflict has an impact on the behavior of depression either direct or mediated by job satisfaction and life satisfaction. Our findings bear out the notion that job satisfaction and life satisfaction mediates the influence of dual role conflict on depression, highlighting the effect of individual satisfaction within this area. The suggestions for nurses, they should improve job satisfaction and life satisfaction so that it can overcome the dual role conflict they suffered.